Demoralization syndrome in elderly patients with advanced lung cancer: a multi-center study in North China - Li, Ya; Yang, Wei; Feng, Weiwei; Zhang, Lingyuan; Yao, Yikun; Yan, Kai; Zhang, Hong; Wan, Xiaochao (Frontiers in Medicine, 2025)
ObjectiveThis observational study sought to explore the prevalence and determinants of demoralization syndrome (DS) among elderly patients in North China diagnosed with advanced lung cancer (ALC), with the primary goal of mitigating their psychological distress.MethodsA convenience sampling approach was employed to recruit 420 ALC patients aged 60 years or older from four tertiary hospitals in North China. Data collection was carried out using structured questionnaires, which included the Chinese adaptation of the Demoralization Syndrome Scale and Perceptions of Social Support Questionnaire. Statistical analyses were performed using SPSS 26.0 software to derive meaningful insights.ResultsUnivariate analysis identified several significant factors influencing DS levels, including gender, smoking, average monthly household income, living alone, stage of cancer, social support, and self-management abilities. The mean DS score was notably elevated, with 32.8% of participants scoring within the high DS range. Multivariable linear regression analysis further established gender, average monthly household income, stage of cancer, social support, and self-management abilities as independent predictors of DS severity.ConclusionThe findings highlight the critical importance of addressing socioeconomic factors such as household income, strengthening social support networks, improving self-management skills, and implementing targeted interventions for female patients to reduce DS levels and alleviate psychological distress in elderly ALC patients, particularly those with stage IV cancer. These insights provide valuable guidance for healthcare professionals aiming to enhance the overall well-being of this high-risk population.